Screw loosening of different UCLA-type abutments after mechanical cycling - Marcela C. Junqueira; Ricardo F. Ribeiro; Adriana Claudia L. Faria; Ana Paula Macedo; Rossana P. Almeida (Universidade Estadual de Campinas, 2015)
Aim: To evaluate the loss of applied torque (detorque) values in cast and pre-machined abutments for external hex abutment/implant interface of single implant-supported prostheses subjected to mechanical cycling. Methods: Ten metal crowns were fabricated using two types of UCLA abutments: cast and pre-machined with metal base in NiCrTi alloy and tightened to regular external hex implants with a titanium alloy screw, with an insertion torque of 32 N.cm, measured with a digital torque gauge. Samples were embedded with autopolymerizing acrylic resin in a stainless steel cylindrical matrix, and positioned in an electromechanical machine. Dynamic oblique loading of 120 N was applied during 5 x 105 cycles. Then, each sample was removed from the resin and detorque values were measured using the same digital torque gauge. The difference of the initial (torque) and final (detorque) measurement was registered and the results were expressed as percentage of initial torque. The results of torque loss were expressed as percentage of the initial torque and subjected to statistical analysis by the Student's t-test (p<0.05) for comparisons between the test groups. Results: Statistical analysis demonstrated that mechanical cycling reduced the torque of abutments without significant difference between cast or pre-machined UCLA abutments (p=0.908). Conclusions: Within the limitations of this in vitro study, it may be concluded that the mechanical cycling, corresponding to one-year use, reduced the torque of the samples regardless if cast or pre-machined UCLA abutments were used.